Image of Suswani Ma inside the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
Main shrine image of Suswani Ma inside the garbhagriha (sanctum sanctorum) of the Suswani Mata Temple. The image, covered in drapery, is shown sitting on a rectangular pedestal.